2022
DOI: 10.1021/acssuschemeng.1c07907
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced N- and B-Codoped Graphene Nanozymes with Intrinsic Peroxidase-Like Activities for Bactericidal Application

Abstract: Conventional heteroatom-doped graphene oxide (GO) nanozymes usually suffer from complicated manufacturing processes and difficult recovery of nanozymes. Herein, a facile and ecofriendly approach is developed to write nitrogen- and boron-codoped GO nanozyme patterns on a flexible plastic film by CO2 laser scanning in ambient air without any catalyst, mask, or template. The resulting N-doped laser-induced graphene (LIG) with a hierarchical porous and hydrophilic interface possesses intrinsic peroxidase-like acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…It is very noteworthy that multi-element co-doping is more effective than single element doping due to the synergistic effect of co-doped elements, which can form stronger active regions on its surface [ 29 , 88 ]. An LIG co-doped with N and B (NB-dLIG) was reported in a recently published article [ 29 ].…”
Section: Process Control Of Ligmentioning
confidence: 99%
“…It is very noteworthy that multi-element co-doping is more effective than single element doping due to the synergistic effect of co-doped elements, which can form stronger active regions on its surface [ 29 , 88 ]. An LIG co-doped with N and B (NB-dLIG) was reported in a recently published article [ 29 ].…”
Section: Process Control Of Ligmentioning
confidence: 99%
“…Cys-Ru NS oxidase and peroxidase-like activities are compared under the optimized reaction conditions (Figure d). The addition of Cys-Ru NSs to TMB solution does not show any significant color change, revealing negligible oxidase-like activity . In contrast, adding Cys-Ru NSs to TMB solution containing H 2 O 2 resulted in rapid formation of a dark-blue product (oxidized TMB), indicating strong peroxidase-like activity.…”
Section: Resultsmentioning
confidence: 92%
“…The addition of Cys-Ru NSs to TMB solution does not show any significant color change, revealing negligible oxidase-like activity. 39 In contrast, adding Cys-Ru NSs to TMB solution containing H 2 O 2 resulted in rapid formation of a dark-blue product (oxidized TMB), indicating strong peroxidase-like activity. Furthermore, Cys-Ru NSs were demonstrated to have maximum peroxidase-like activity in acetate buffer (pH 5) at 50 °C (Figure S3a).…”
Section: Optimization Of Reaction Conditions For Peroxidase-like Acti...mentioning
confidence: 99%
“…S4, ESI†) confirmed that the LIFeG nanozyme consisted of N-dopant in the LIG carbon structure, which is in good agreement with the earlier report. 14 The TEM image of LIFeG nanozyme in Fig. 2A demonstrates the good dispersion of small Fe 3 O 4 nanoparticles, with diameters of around 5–50 nm, on the surface of a multi-layered LIG nanosheet.…”
mentioning
confidence: 93%
“…11–13 Recently, our group has demonstrated that LIG with inherent N-doping possesses an intrinsic POD-like catalyst and thus can be used for killing bacteria. 14 However, the ability of using LIG itself as a nanozyme to effectively combat bacteria at a low concentration of H 2 O 2 without external energy input is still unsatisfactory due to its low POD-like catalytic activity. Nevertheless, its 3D interconnected macroporous framework structure, large specific surface area, high electronic conductivity, abundant edge-plane defects, and good photothermal properties make LIG an appropriate and appealing supportive matrix for nanozymes to fabricate LIG-based nanocomposites, 15 providing a potential route for the development of LIG-nanozyme hybrids to enhance the bactericidal capacity by adopting catalytic–photothermal synergetic effects.…”
mentioning
confidence: 99%